Using SimCLIM for Modelling the Impacts of Climate Extremes in a Changing Climate: A Preliminary Case Study of Household Water Harvesting in Southeast Queensland - Warrick, Richard (Modelling and Simulation Society of Australia and New Zealand Inc. (MSSANZ), 2009)
The aim of this paper is to present and demonstrate features of the integrated SimCLIM modelling system for assessing impacts and risks of climatic extremes in a changing climate. Features of the model that can be used for risk-based analyses are first described briefly, and are then illustrated by an analysis of the risk of rainfall variability and extremes on household water tank systems. SimCLIM is an “open-framework” software modelling system that can be customised and maintained by users for the purpose of examining the impacts and adaptations to climate variability and change, including extreme climatic events. SimCLIM contains tools for both spatial and site time-series analyses. The core features of SimCLIM that are directly relevant to risk-based climate impact assessments are its scenario generator and its extreme event analyser. In SimCLIM, the two are linked, so that estimates of the return periods for extreme events (e.g. heavy daily rainfall events) can be assessed under both current climate and under scenarios of climate change. Time-series data perturbed by the scenario generator within SimCLIM are used to drive various impact models. In this way, the data are “processed” and the extreme events become manifested as outputs of those models. Using a water tank model “plugged-in” to SimCLIM, a preliminary case study was conducted of the effects of low rainfall conditions on household water tank systems in an area of Southeast Queensland and northern NSW centred on Brisbane. With the simplifying assumption that the storage tank is the sole source of water, the risks – expressed in terms of the number of occurrences of an empty tank and the longest period without water – were assessed under both present climate variability and future scenario of climate change for 2050 based on an ensemble of eight GCM patterns. The model was run for 30 years of daily rainfall data for 37 stations and the results were spatially interpolated to produce risk maps. It was found that the risks vary greatly over the region, with a steep east-west risk gradient quickly transitioning from a large area of low risk to a large area of extreme risk. The simulation under a scenario of climate change, which produced drier conditions in the region by 2050, resulted in an eastward shift of the relatively narrow risk transition zone, with incursion of higher risk toward the more heavily populated coastal areas. This preliminary study suggests that the spatial differences in the risk of tank system failure due to drought occurrences are so large that drastically different designs could be warranted over rather short distances. Simulation models that systemically assess the effects of climate variability and change could provide a basis for informing decisions regarding: (1) the advisability of tank systems for a given location as compared to other sources; (2) the system components that could be adjusted to reduce risks of failure; and (3) the degree of risk that would be acceptable to homeowners. As shown here, integrated modelling systems like SimCLIM can contribute to such assessments.